2013
DOI: 10.1155/2013/670914
|View full text |Cite
|
Sign up to set email alerts
|

Ion Dynamics Study of Potato Starch + Sodium Salts Electrolyte System

Abstract: The effect of different anions, namely,SCN−,I−, andClO4−, on the electrical properties of starch-based polymer electrolytes has been studied. Anion size and conductivity are having an inverse trend indicating systems to be predominantly anionic conductor. Impact of anion size and multiplet forming tendency is reflected in number of charge carriers and mobility, respectively. Ion dynamics study reveals the presence of different mechanisms in different frequency ranges. Interestingly, superlinear power law (SLPL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…The s parameters can be interpreted by different power laws for frequency dependent conductivity; for dc conductivity s parameter value is 0 [21] and for Correlated Barrier Hoping (CBH) Mechanism values 0 < s < 1 [22]. According to the values of exponent ''s'' varying from 0 to 0.7 are shown in the Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The s parameters can be interpreted by different power laws for frequency dependent conductivity; for dc conductivity s parameter value is 0 [21] and for Correlated Barrier Hoping (CBH) Mechanism values 0 < s < 1 [22]. According to the values of exponent ''s'' varying from 0 to 0.7 are shown in the Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…SPEs have garnered significant attention owing to their appealing properties, including their ease of transformation into thin films, good mechanical behavior, electrochemical stability, well-defined electrode/electrolyte interface, safety, and no leakage [44]. These characteristics are in stark contrast with those of liquid electrolytes.…”
Section: Solid Polymers Electrolytes (Spes)mentioning
confidence: 99%
“…In 2013, Tiwari et al [44] reported on starch-based sodium PEs. Potato starch was mixed with NaI, NaSCN, and NaClO 4 salts, and the effects of different anions were studied.…”
Section: Solid Polymers Electrolytes (Spes)mentioning
confidence: 99%
“…Commonly, most of the previous works used an inorganic polymer and inorganic solvent as starting materials in SPE film preparation. Nowadays, the usage of natural polymers such as starch, chitosan and cellulose had gained much attention among researchers due to its nature properties (environmental friendly and inexpensive) [6][7][8]. The selection of relevant initial materials in SPE production at the major stage can directly improve the physical, chemical and electrical properties of SPE film itself and also could cut the cost of production.…”
Section: Introductionmentioning
confidence: 99%